Evolution of an Improved Trawl for Traditional Motorised Craft - V., Vijayan; M.D., Varghese; V.C., George; G.R., Unnithan (Fishery Technology, 2025)
12.77 m two seam trawl net designed for operation from 8.40 m OAL dug out canoe with 11HP outboard engine was field tested and the results compared, with 14.00 m two seam trawl net commonly used in Valappu area of Vypeen Island. The former net brought in 31.5 % more shrimp catch and 37% more revenue compared to the latter. Selective action of square meshes in cod end was also attempted.